Reinvestigating the Oil Dependency of the GCC Countries’ Stock Market: A Regime-Switching Cointegration Approach - Ebadi, Esmaeil; Razaq, Yousef Abdul (International Journal of Energy Economics and Policy, 2024)
This paper investigates the asymmetric impact of oil prices on Gulf Cooperation Council (GCC) stock markets using a regime-switching cointegration approach with data from April 2012 to April 2022. we postulate that investors consider ups and downs in the stock market index instead of price-earnings ratios in their decision-making process. Our results indicate that investors exhibit more optimism during economic upturns, corresponding to positive oil shocks, than pessimism during economic downturns. The study offers several contributions to the literature: (i) Diagnostic tests affirm that constructing the model based on stock market index movements rather than P/E ratios results in superior performance. (ii) As expected for oil-dependent nations, our model attributes more significant deterministic influence to the oil market and closely tracks the stock market. (iii) The results demonstrate that positive oil shocks exert a more pronounced long-term asymmetric influence on GCC stock markets than adverse shocks. (iv) Dynamic multiplier analysis reveals that oil shocks persist longer in Oman, Bahrain, and Qatar’s markets than in the UAE, Saudi Arabia, and Kuwait. (v) The stock market in the United Arab Emirates exhibits greater independence from oil price fluctuations, responding modestly, while Qatar and Bahrain markets are more sensitive.